1996
DOI: 10.1056/nejm199601183340304
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Fecal Occult-Blood Tests for Colorectal-Cancer Screening

Abstract: HemeSelect and a combination test in which HemeSelect is used to confirm positive Hemoccult II Sensa results improve on Hemoccult II in screening patients for colorectal carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
332
5
18

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 562 publications
(366 citation statements)
references
References 16 publications
11
332
5
18
Order By: Relevance
“…8 A factor driving increased colonoscopic use is that advanced colonic neoplasms may be missed by a 1-time GFOBT screen. One-time sensitivity of the original GFOBT Hemoccult II (Beckman Coulter, Fullerton, California) for cancer appears to be less than 50% 13 and perhaps even lower. 14 Another study observed that 24% of advanced neoplasms are missed by 1-time GFOBT plus flexible sigmoidoscopy.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…8 A factor driving increased colonoscopic use is that advanced colonic neoplasms may be missed by a 1-time GFOBT screen. One-time sensitivity of the original GFOBT Hemoccult II (Beckman Coulter, Fullerton, California) for cancer appears to be less than 50% 13 and perhaps even lower. 14 Another study observed that 24% of advanced neoplasms are missed by 1-time GFOBT plus flexible sigmoidoscopy.…”
mentioning
confidence: 95%
“…12 To improve sensitivity of GFOBT, rehydration has been used, 3 and newer GFOBT have been specifically designed to be more sensitive and readable. 13,15,16,17 The logistics of performing GFOBTs also lead to questions concerning their usefulness. 1,16 GFOBTs detect peroxidase activity of heme in feces.…”
mentioning
confidence: 99%
“…This is particularly relevant when other better options are available for stool testing for CRC namely IFOBT (Allison et al, 1996;Morikawa et al, 2005) and should have been discussed by the authors. These ELISAbased IFOBTs (Allison et al, 1996) or automatically analysable IFOBT (Morikawa et al, 2005) have demonstrated sensitivity of around 60% and specificity of about 90%.…”
Section: Sirmentioning
confidence: 99%
“…This is particularly relevant when other better options are available for stool testing for CRC namely IFOBT (Allison et al, 1996;Morikawa et al, 2005) and should have been discussed by the authors. These ELISAbased IFOBTs (Allison et al, 1996) or automatically analysable IFOBT (Morikawa et al, 2005) have demonstrated sensitivity of around 60% and specificity of about 90%. Recently various 'office based or bedside' simple, convenient and cheap strip-based IFOBT have been validated for CRC screening with performance characteristics similar to that of an ELISA-based IFOBT (Hoepffner et al, 2006;Smith et al, 2006).…”
mentioning
confidence: 99%
“…To screen for colorectal diseases, immunological fecal occult blood tests using fecal hemoglobin (Hb) as a marker are widely performed (1)(2)(3)(4). However, Hb is unstable in feces, leading to false-negative results, and this test is of no use for the detection of lesions without bleeding.…”
Section: Introductionmentioning
confidence: 99%